The Exploration Study of Entrepreneurial Leadership as Strategic Asset in Ciputra Group - Lily Ambarwati Saksono; Burhan Bungin; Denny Bernardus (Binus Business Review, 2025)
In the era of the Industrial Revolution 4.0, which is full of uncertainty, a leader who has a combination of leadership qualities and entrepreneurial spirit is needed for organizational growth, development, and sustainability. The research explored the dimensions of entrepreneurial leadership exemplified by Ciputra, the founder of Ciputra Group. It explored how these dimensions influenced the behavior of leaders who interacted directly with him. The research applied a post-positivist qualitative approach with a Simple Research Design (SRD) and the Coding Color Analysis Procedure (CCAP) to analyze the data. The primary data collection method was conducted through interviews with five informants. The results identify 10 dimensions of entrepreneurial leadership, including resilience, which has yet to be highlighted in previous related research. Resilience, in particular, is notably present among Ciputra Group leaders. Additionally, the results reveal five influences of Ciputra in entrepreneurial leadership dimensions on the behavior of leaders who interact directly with him. The findings are intended to inspire and provide valuable insights to leaders, especially founders, seeking to enhance their organizational performance and sustainability. By understanding and adopting these entrepreneurial leadership dimensions, leaders can better navigate the complexities of today’s business environment and drive their organizations toward tremendous success.